Resistance to Antibacterial Preparations of H. Pylori, Allocated in Patients With (Malt) Gastric Lymphoma - Nuruzova Z. A., Jumamurodov S. T. (International Journal of Advanced Science and Technology, 2020)
The article presents the results of a bacteriological study of H. pylori strains isolated from patients with gastric MALT lymphoma treated in cancer centers in the city of Tashkent. Antibiotic resistance was detected by the disk diffusion method for first-line drugs used in the eradication therapy of H. pylori strains: amoxicillin, clarithromycin, levofloxacin, metronidazole, tetracycline, as well as doxycycline, rifampicin and chloramphenicol. A high level of resistance to chloramphenicol, doxycycline and rifampicin was revealed. There was an increase in resistance to metronidazole (20% of strains), amoxicillin (17.7%) and clarithromycin (15.6% of resistant strains), i.e. on the border of permissible limits, which dictates the need for an individual approach to caradication therapy, with the obligatory bacteriological isolation of the pathogen to determine antibiotic resistance.